Goal scoring patterns in the FIFA World Cup 2022 group stage: more goals by substitute players, but no effect of more stoppage time - Wei, X.; Zhao, Y.; Chen, H.; Chmura, P.; Randers, M. B.; Krustrup, P. (The Journal of Sports Medicine and Physical Fitness, 2024)
BACKGROUND: The 2022 World Cup introduced new substitution rules, tournament periods and stoppage time calculation methods. Thus, the aim of this study was to analyze the goal time characteristics during the FIFA World Cup 2022 group stage in comparison with those of the 2018 event, exploring the potential influence on the goal times after the new substitution rules, stoppage time calculation method, and tournament periods. METHODS: A total of 242 goals were used for analysis. The timing, zones and ways of goals scored were used for the analyses by X2 Test with a significance level set at P<0.05. RESULTS: More goals were scored in the second half than in the first half (64.2% vs. 35.8%; X2=9.633, P<0.05) and a significant difference in the goals scored in 15 minutes intervals in 2022 World Cup group stage (X2=16.000, P<0.05). No difference were observed in the goal scoring time in two World Cups in terms of the different intervals, results, areas, and ways (P>0.05), but more open play goals were scored in the 2022 event (X2=10.200, P<0.05) and substitutes scored more goals in the 2022 World Cup group stage as compared to those in the 2018 event (X2=5.161, P<0.05). Despite more stoppage time in the 2022 event than in the 2018 event (11.6 vs. 7.3 min), no differences were observed in the number of goals scored in stoppage time (X2=0.953, P>0.05). CONCLUSIONS: This study highlights the importance of the insight of goal scoring pattern. Practitioners need to allocate physical fitness to tactical arrangements in a reasonable manner according to the time of the game, improve open play scoring ability and increase substitution awareness.